2019
DOI: 10.1128/jvi.01161-19
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Induces Brain Inflammation and Multifocal Demyelination in the Cotton Rat Sigmodon hispidus

Abstract: Our work demonstrates for the first time a direct association between infection with herpes simplex virus 1, a ubiquitous human pathogen generally associated with facial cold sores, and multifocal brain demyelination in an otherwise normal host, the cotton rat Sigmodon hispidus. For a long time, demyelinating diseases were considered to be autoimmune in nature and were studied by indirect methods, such as immunizing animals with myelin components or feeding them toxic substances that induce demyelination. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 66 publications
(82 reference statements)
2
21
0
Order By: Relevance
“… 74 , 75 The main type of immunity that is activated is the innate immune response (the most rapid defense system for the host cell) to combat HSV-1 infection, 76 as demonstrated in hispid cotton rat ( Sigmodon hispidus) displaying brain inflammation and multifocal demyelination caused by HSV-1. 77 …”
Section: Hsv-1 and Enhanced Inflammation In Admentioning
confidence: 99%
“… 74 , 75 The main type of immunity that is activated is the innate immune response (the most rapid defense system for the host cell) to combat HSV-1 infection, 76 as demonstrated in hispid cotton rat ( Sigmodon hispidus) displaying brain inflammation and multifocal demyelination caused by HSV-1. 77 …”
Section: Hsv-1 and Enhanced Inflammation In Admentioning
confidence: 99%
“…Regarding herpesviruses, the majority of which are ubiquitous viruses, they are known to infect and persist in several cell types, and the chronic infection that they cause may induce long lasting or chronic inflammation in several tissues. This facilitates the onset of a variety of inflammation-based diseases ranging from gastritis, inflammatory bowel diseases, autoimmune diseases, neurodegenerative diseases, and cancer [ 33 , 37 , 38 , 39 ]. Other completely different viruses such as hepatitis viruses may also cause diseases, to whose pathogenesis the inflammatory response strongly contributes.…”
Section: Targeting Upr or Prr Signaling To Mitigate Excessive Inflammmentioning
confidence: 99%
“…Demyelinating lesions have also been associated with HSV-1-induced facial nerve paralysis [ 113 ]. A recent study demonstrated a direct association between infection with HSV-1 and multifocal brain demyelination in a murine model [ 114 ]. Moreover, in that study, demyelination was followed by remyelination, although it was incomplete and the presence of scars was observed.…”
Section: Hsv-1 and Demyelinationmentioning
confidence: 99%